Implementation of Controlled Islanding Scheme for Self-healing Smart Grid - Khair, Abul; Rihan, Mohd; Zuhaib, Mohd (International Journal of Engineering and Technology, 2018)
With increase in deregulations and renewable sources of generation, the power system network is leading towards more geographical spread and interconnectedness. This causes significant challenges requiring on-line monitoring and control. It also provides a path for disturbances to propagate causing cascading failure, even blackouts. Wide area detection of potential island formation and controlled separation is considered as an effective tool against a blackout under severe disturbances. In the present work one line remaining algorithm has been utilized for implementation of controlled islanding in a section of Indian power grid.Â Â